2020
DOI: 10.1186/s12913-020-4920-5
|View full text |Cite
|
Sign up to set email alerts
|

Pilot trial of The Living Well Toolkit: qualitative analysis and implications for refinement and future implementation

Abstract: Background: Following a neurological event, people's long-term health and well-being is hampered by a system that struggles to deliver person-centred communication and coordinated care and fails to harness individual and family capability to live well with the condition. We aimed to implement and evaluate a toolkit package to support these processes for people with long-term neurological conditions. Methods: This is a multi-phased study drawing on the principles of participatory research. In this pilot phase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In line with these attributes' merits, a recent systematic review showed that barriers might hinder LHS 36,3 toolkit uptake consisted of but not limited to time restrictions, costs, difficulty to use and dissatisfaction with the toolkit's content (Hempel et al, 2019). The iterative refinement process suggests that the continuous supports tailored to organizations' needs likely increases a toolkit's uptake (Mudge et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In line with these attributes' merits, a recent systematic review showed that barriers might hinder LHS 36,3 toolkit uptake consisted of but not limited to time restrictions, costs, difficulty to use and dissatisfaction with the toolkit's content (Hempel et al, 2019). The iterative refinement process suggests that the continuous supports tailored to organizations' needs likely increases a toolkit's uptake (Mudge et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are calls to move away from seeing biomedical approaches and person-centred care as dichotomous but rather on a continuum (Mudge et al, 2020;Terry and Kayes, 2019). Adopting a view of person-centredness as a continuum would encourage an understanding that improvements are possible (Mudge et al, 2020;Terry and Kayes, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are calls to move away from seeing biomedical approaches and person-centred care as dichotomous but rather on a continuum (Mudge et al, 2020;Terry and Kayes, 2019). Adopting a view of person-centredness as a continuum would encourage an understanding that improvements are possible (Mudge et al, 2020;Terry and Kayes, 2019). This view would help physiotherapists make small, incremental changes within biomedical healthcare environments, towards approaches that support the empowerment of patients in actively selfmanaging their long-term conditions such as seeking to involve patients in decision making or seeing patients as people and collaborative partners.…”
Section: Discussionmentioning
confidence: 99%
“…This could indicate that practitioners were aware of patient choice and autonomy, or suggestive of a paternalistic, reductionist approach to exercise for falls prevention which was not as patient centred as was first thought. It is important to recognise that views on person-centredness are on a continuum and as such practitioners will be at varying points on that continuum [19,20].…”
Section: Discussionmentioning
confidence: 99%